2013
DOI: 10.1093/infdis/jit472
|View full text |Cite
|
Sign up to set email alerts
|

Genital Herpes Simplex Virus Type 2 Infection in Humanized HIV-Transgenic Mice Triggers HIV Shedding and Is Associated With Greater Neurological Disease

Abstract: JR-CSF/hu-cycT1 mice provide a valuable model to study HIV/HSV-2 coinfection and identify potential mechanisms by which HSV-2 facilitates HIV-1 transmission and HIV modulates HSV-2-mediated disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…One possible mechanism that may have contributed to the increased HIV-1 infection in HSV-2-infected hCD4/R5/cT1 mice after intravaginal inoculation is HSV-2-mediated secretion of chemokines and cytokines, which recruited CD4 ϩ T cells, dendritic cells, and/or macrophages to the submucosal site of HSV-2 infection (11,12). An influx of HIV-1-susceptible cells into the submucosal tissues would provide more infectible targets for HIV-1, thereby facilitating both the establishment and dissemination of HIV-1 infection.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One possible mechanism that may have contributed to the increased HIV-1 infection in HSV-2-infected hCD4/R5/cT1 mice after intravaginal inoculation is HSV-2-mediated secretion of chemokines and cytokines, which recruited CD4 ϩ T cells, dendritic cells, and/or macrophages to the submucosal site of HSV-2 infection (11,12). An influx of HIV-1-susceptible cells into the submucosal tissues would provide more infectible targets for HIV-1, thereby facilitating both the establishment and dissemination of HIV-1 infection.…”
Section: Resultsmentioning
confidence: 99%
“…In our transgenic mouse model, HSV-2-challenged hCD4/R5/cT1 mice displayed increased levels of HIV-1 infection in the lower genital tract mucosa and increased dissemination of HIV-1 infection into the draining lymph nodes. We previously reported that HSV-2 infection of C57BL/6 mice induced an increase in interleukin-1␤ (IL-1␤), tumor necrosis factor alpha (TNF-␣), IL-1␣, monocyte chemotactic protein 1 (MCP-1), macrophage inflammatory protein 1␤ (MIP-1␤), and RANTES gene expression in the lower genital tract mucosa 2 days after infection (12). MCP-1, MIP-1␤, and RANTES are chemokines that stimulate the recruitment of T cells and monocytes (54,55).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thanks to the implementation of a murine model that recapitulates the higher susceptibility to acquire HIV after HSV-2 infection, new molecular mechanisms that relate both viruses will likely be identified in the near future [124].…”
Section: Relationship Between Hsv-2 and Hivmentioning
confidence: 99%